Answer:
x = 0, x = -4, and x = 6
Step-by-step explanation:
To find the zeros of this polynomial, we can begin by factoring out a common factor of each term. 'x' is a common factor. We can distribute this variable out, giving us:
f(x) = x(x²- 2x- 24)
Now, factor the polynomial inside of the parenthesis into its simplest form. Factors of -24 that add up to -2 are -4 and 6.
f(x) = x( x + 4) (x - 6)
From this, we can derive the zeros x = 0, x = -4 and x = 6.
Answer:
a
Step-by-step explanation:
Answer:
the picture is blurry
Step-by-step explanation:
<h2>can. you give me another picture? plz</h2>
Answer:
That means that each water is $2.50, das crazy tho
Step-by-step explanation: